2021
DOI: 10.1002/ar.24758
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic effect and methods of traditional Chinese medicine on COVID‐19‐induced depression: A review

Abstract: has spread all over the world with a high infection rate. Currently, there are no targeted therapeutic drugs for COVID-19 as well as for stress induced by COVID-19. The unpredictable events of COVID-19 can trigger feelings of fear, worry, or unease in people, leading to stress-related disorders such as depression and anxiety. It has been reported that individuals, including COVID-19 patients, medical staff, and ordinary people, are under both physical and psychological pressure, and many of them have developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…Moreover, there was significant improvement of Sahaj Samadhi meditation on the Hamilton rating scale for depression in old patients during the COVID-19 period (110). Traditional Chinese herb formulations, such as Chaihu Shugan San, Xiaoyao San, and Sini San were proved to be effective to reduce depressive symptoms in patients infected with COVID-19 virus (111). Moreover, acupuncture was proofed not only to relief primary and secondary depressive symptoms, but also to reduce the side effects of the medical treatments (112).…”
Section: Complementary and Integrative Therapiesmentioning
confidence: 99%
“…Moreover, there was significant improvement of Sahaj Samadhi meditation on the Hamilton rating scale for depression in old patients during the COVID-19 period (110). Traditional Chinese herb formulations, such as Chaihu Shugan San, Xiaoyao San, and Sini San were proved to be effective to reduce depressive symptoms in patients infected with COVID-19 virus (111). Moreover, acupuncture was proofed not only to relief primary and secondary depressive symptoms, but also to reduce the side effects of the medical treatments (112).…”
Section: Complementary and Integrative Therapiesmentioning
confidence: 99%
“…As is well known, individuals remain in the workforce and have the highest psychological stress responses related to family, economic, and health issues in this stage of life [ 8 , 34 ]. It has also been found that music listening interventions or online music therapies have effects on reducing anxiety, enhancing mood, improving mental health, and supporting subjective wellbeing, not only for coping with diagnosed diseases but also for combating COVID-19-induced mood disturbance or mental stress [ 21 , 26 , 38 ]. Some types of music may actually increase negative emotions, although this differential effect of music has not yet been adequately tested.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Accumulating evidence indicated the favorable therapeutic efficacy of traditional Chinese medicine in treating disease-induced depression, such as post-stroke depression, [12] chronic unpredictable mild stress-induced depression-like behaviors, [13] and COVID-19-induced depression. [14] Traditional Chinese medicine prescription is an effective, low-toxicity, multi-target prescription not only in the treatment of depression but also cancers. For example, a Chinese herbal formulation called Xiaoyao Kangai Jieyu Fang could ameliorate cancer-related depression concurrent with BC by promoting hippocampal synaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%